Reforming the United Nations : Challenge of relevance - "Saksena, K.P" (New Delhi, 1993)
In the context of the dramatic changes in the world order and the ongoing discussions concerning reforming and restructuring the United Nations, this book provides an in-depth analysis of the existing UN framework, how it evolved over the decades, the challenges it is currently confronted with and the alternatives that lie ahead.
Keywords: United Nations-Finance